2020
DOI: 10.1093/jnen/nlaa130
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Traumatic Brain Injury Is Associated With TDP-43 Alterations, Neurodegeneration, and Glial Activation in Mice

Abstract: Increasing evidence points to a relationship between repetitive mild traumatic brain injury (mTBI), the Tar DNA binding protein 43 (TDP-43) pathology and some neurodegenerative diseases, but the underlying pathophysiological mechanisms are still unknown. We examined TDP-43 regulation, neurodegeneration, and glial responses following repetitive mTBI in nontransgenic mice and in animals with overexpression of human mutant TDP-43 protein (TDP-43G348C). In the frontal cortices of the injured nontransgenic animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 94 publications
1
17
0
Order By: Relevance
“…Poorer performance on visible platform trials following multiple CHIMERA injuries has been reported in another recent study, which also found impaired performance on a visual cliff task and reduced visual evoked potentials, providing further evidence for behavioral and physiological visual dysfunction. 38 Like many other murine models of CBI, with or without rotational acceleration, 13,[39][40][41][42]46,[70][71][72] pathological analysis of mice following CHIMERA (including the current study) finds significant and often prolonged increased astrogliosis and/or microgliosis in the optic tracts as assessed by GFAP or Iba1 staining, respectively. 14,38,66 Decreased performance on the optokinetic behavioral response test, coupled with decreases in the number of retinal ganglion cells, has also been reported following single or repeated concussive TBI.…”
Section: Summary Of Pathological Findingsmentioning
confidence: 52%
“…Poorer performance on visible platform trials following multiple CHIMERA injuries has been reported in another recent study, which also found impaired performance on a visual cliff task and reduced visual evoked potentials, providing further evidence for behavioral and physiological visual dysfunction. 38 Like many other murine models of CBI, with or without rotational acceleration, 13,[39][40][41][42]46,[70][71][72] pathological analysis of mice following CHIMERA (including the current study) finds significant and often prolonged increased astrogliosis and/or microgliosis in the optic tracts as assessed by GFAP or Iba1 staining, respectively. 14,38,66 Decreased performance on the optokinetic behavioral response test, coupled with decreases in the number of retinal ganglion cells, has also been reported following single or repeated concussive TBI.…”
Section: Summary Of Pathological Findingsmentioning
confidence: 52%
“…Elevated TDP-43 expression levels in the whole-cell lysates from the injured mouse cortical and hippocampal tissue [ 24 , 25 ], as well as the protein changes in the rat brain following blast TBI [ 26 ], were described. We detected transitory TDP-43 cytoplasmatic translocation and overexpression of the protein and its pathological forms in the frontal cortex within the first week following repetitive mTBI in mice [ 27 ]. Neurodegeneration and gliosis in the optic tracts (OT) of injured wild-type mice and animals with overexpression of human mutant TDP-43 protein (TDP-43 G348C ), a model of ALS/FTLD [ 28 ], were also demonstrated [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…We detected transitory TDP-43 cytoplasmatic translocation and overexpression of the protein and its pathological forms in the frontal cortex within the first week following repetitive mTBI in mice [ 27 ]. Neurodegeneration and gliosis in the optic tracts (OT) of injured wild-type mice and animals with overexpression of human mutant TDP-43 protein (TDP-43 G348C ), a model of ALS/FTLD [ 28 ], were also demonstrated [ 27 ]. In addition, the level of damage in the OT was significantly increased in TDP-43 transgenic animals compared with wild-type mice at the end of the first week after the last injury [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations